Blood lead determinants and the prevalence of neuropsychiatric symptoms in firearm users in Mexico - Guadalupe Aguilar Madrid; Liliana Téllez-Cárdenas; Cuauhtémoc Arturo Juárez-Pérez; Luis Cuauhtémoc Haro-García; Adriana Mercado-García; Rodrigo Gopar-Nieto; Alejandro Cabello-López (International Journal of Occupational Medicine and Environmental Health, 2016)
Objectives: To identify blood lead predictors and the prevalence of neuropsychiatric symptoms in firearm users of public security in Mexico. Material and Methods: A cross-sectional study was performed on 65 males. We obtained socio-occupational data and determined venous blood lead (blood (B), lead (Pb) – BPb), as well as neuropsychiatric symptoms using the Q-16 questionnaire. A multiple linear regression model was constructed to assess determinants of BPb. Results: The mean age in the study group was 34.8 years (standard deviation (SD) = 6.9, range: 21–60); the mean number of years spent in the company amounted to 14 years (SD = 8.5, range: 1–48). Twenty percent of the respondents (N = 13) used leaded glazed clay pottery (lead (Pb), glazed (G), and clay pottery (C) – PbGC) in the kitchen. During practice they fired a mean of 72 shots (SD = 60, range: 20–250), and during their whole duration of employment 5483 shots (SD = 8322.5, range: 200–50 000). The mean BPb was 7.6 μg/dl (SD = 6.8, range: 2.7–51.7). Two caretakers from the firing range had 29.6 μg/dl and 51.7 μg/dl BPb. The subjects who had shooting practice sessions ≥ 12 times a year reported a greater percentage of miscarriages in their partners (24% vs. 0%). Twelve percent of the respondents showed an increase in neuropsychiatric symptoms. The BPb multiple linear regression model explained R2 = 44.15%, as follows: those who had ≥ 12 practice sessions per year – β = 0.5339 and those who used PbGC – β = 0.3651. Conclusions: Using firearms and PbGC contributes to the increased BPb in the studied personnel. The determinants of BPb were: shooting practices >12 times a year and using PbGC. Blood lead concentrations reported in the study, despite being low, are a health risk, as evidenced by the prevalence of neuropsychiatric symptoms.